Effectiveness of Slow Stroke Back Massage Therapy on the Sleep Quality of Postpartu Mother - Sihaloho, Endang; Dalimunthe, Selvian Yolanda; Simamora, Mery Krista; Ristiani, Ristiani (Global Health Science Group, 2022)
The risk factors for non-typhoidal Salmonella infections in pediatric populations are not fully understood, but this remains a critical area of study for improving child health. Objective: The aim of this review is to systematically analyze the available literature about the risk factors of non typhoidal salmonella among pediatric populations. Method: The risk factors for non-typhoidal Salmonella infections in children were examined in all papers published between 2019 and 2024 using a systematic review of the literature using PRISMA criteria. Google Scholar, PubMed, and ProQuest are the three electronic databases that the writers searched. The query